P PENGARUH PELATIHAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. BANK PERKREDITAN RAKYAT MAJALENGKA JABAR: Pelatihan; Kompensasi; Kinerja Karyawan - Wibowo, Sandi Nasrudin Wibowo; Amalia, Devina; Nurdiana, Editya (Jurnal Ekonomika dan Bisnis Islam, 2022)
PT Bank Perkreditan Rakyat Majalengka is a Regional Owned Enterprise (BUMD) that provides savings and loan services. In providing the best service for customers, it is necessary to have employees who have optimal performance as well. One of the ways to improve employee performance is by training and providing burdens for employees. The purpose of this research is to identify and analyze the effect of training on employee performance. This type of research used is quantitative research with instruments using questionnaires. The research population is all employees of PT Bank Perkreditan Rakyat Majalengka, totaling 58 employees and the sampling technique used is Saturated Sampling. Methods of data analysis using multiple linear regression model using SPSS software. The results of the study show that training has a partial effect on employee performance. This is evidenced by a significance value of 0.000 <0.05 and tcount > ttable (7.017 > 0.000). Meanwhile, the alarm also has a partial effect with a significance value of 0.000 <0.05 and tcount > ttable (5.897 > 2.003). Meanwhile, simultaneously training and influence have a positive and significant effect on employee performance as evidenced by a determination coefficient of 0.494 or 49.4%.